QUALITY OF SOYBEAN GRAINS STORED IN LOW TEMPERATURES - Coradi, P. C.; Milane, L. V.; Camilo, L. J.; Prado, R. L. F.; Fernandes, T. C. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The aim of this study was to evaluate the quality of soybeans stored for six months in an environment with low temperatures and in different packaging. The experimental design was completely randomized, factorial (2x3x2), two types of packaging (permeable paper bags and polyethylene plastic bags) three packaging temperatures (3, 10, and 23 °C) and two times of evaluation (zero and six months). The increased storage time reduced quality of soybeans, regardless of storage conditions and packaging. Storage in permeable packaging affected more the quality of soybeans. The storage temperature of 23 °C was the most negatively alter the quality of soybeans. Storage in air temperature of 3 °C was most favorable for the quality of soybeans, although some quality results were similar, with storage at 10 °C. In conclusion, the artificial cooling of the storage environment to temperatures below 10 °C can be the best alternative to preserve the quality of stored grain. The impermeable packaging for the same average conditions of temperature and relative humidity of the air storage can help to minimize losses in soybeans, in comparison with permeable packings, considering the quality parameters analyzed.